2018
DOI: 10.26459/hueuni-jard.v127i3b.4411
|View full text |Cite
|
Sign up to set email alerts
|

Ảnh Hưởng Của Phương Thức Sử Dụng Chế Phẩm Hb 101 Và Liều Lượng Phân Đạm Đến Sinh Trưởng Và Năng Suất Của Cây Xà Lách (Lactuca Sativa Var. Capitata L.) Trồng Tại Tỉnh Gia Lai

Abstract: Tóm tắt: Một thí nghiệm 2 yếu tố đã được bố trí theo kiểu khối đầy đủ ngẫu nhiên với 3 lần lặp lại trên cây xà lách (Lactuca sativa var. capitata L.) trồng tại tỉnh Gia Lai. Yếu tố A là 2 mức đạm bón: (1) 60 kg/ha, (2) 80 kg/ha; yếu tố B là phương thức sử dụng HB 101: (1) không sử dụng HB 101 – Phun nước lã (ĐC), (2) sử dụng HB 101 tưới vào đất, (3) sử dụng HB 101 tưới vào đất + phun lên cây 3 lần; và (4) sử dụng HB 101 phun lên cây 3 lần. Mục tiêu của nghiên cứu là tìm liều lượng đạm bón và phương thức sử dụn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…Gifford and Jenkins [26] reported that leaf area was the powerful determinant of variation in growth rate. Moringa leaf extracts have high nitrogen content, which is important for the rapid growth and best possible production of crops Tam and Cong [27] Hoa and Thanh [28]. In addition, moringa plant extracts also contain various antioxidant compounds like zeatin, ascorbic acid, phenolic, flavonoids, vitamin E, minerals, and many other growth hormones like indole-3-acetic acid (IAA), and gibberellins (GAs) [29,30].…”
Section: Crop Growth Rate and Relative Growth Ratementioning
confidence: 99%
“…Gifford and Jenkins [26] reported that leaf area was the powerful determinant of variation in growth rate. Moringa leaf extracts have high nitrogen content, which is important for the rapid growth and best possible production of crops Tam and Cong [27] Hoa and Thanh [28]. In addition, moringa plant extracts also contain various antioxidant compounds like zeatin, ascorbic acid, phenolic, flavonoids, vitamin E, minerals, and many other growth hormones like indole-3-acetic acid (IAA), and gibberellins (GAs) [29,30].…”
Section: Crop Growth Rate and Relative Growth Ratementioning
confidence: 99%